Правове регулювання в контексті дії права та його основоположних принципів - Котенко, О.А. (Альманах права, 2012)
Проблеми ефективності правового регулювання, дієвості права, умови та тенденції цих процесів є неможливими без ретельного вивчення їх взаємозв’язку з основоположними принципами сучасного права. Проблемы эффективности правового регулирования, действенности права, условия и тенденции этих процессов невозможны без тщательного изучения их взаимосвязи с основополагающими принципами современного права. One of substantial issue of legal science remains not only definition of the conception of law but its substance and assignment for actual long-term conditions. Direction of the whole legal system development and definition of problems in context of increasing level and efficiency of law depends on solving the methodological problem. Social and legal regulation, influence of law aren’t scientific categories which can by sufficiently explored by present juristic science. However, it is surely can stats the issue of effective performance by social regulators of their most important functions (regulation and protection) is not explored completely even in publication today, especially when it means interconnection of legal regulation, law effectiveness and basic principles of law. Today the influence of law is massive as never before because law becomes not only managing instrument but as a system of basic rights, liberties and liabilities. The understanding of legal influence becomes important and it will help not only in its exploring and cognition but will be reliable theoretical base for practicing lawyer in his law-protecting and law-applying activity. The clarity of law understanding is obligatory stage of clarity and order in social relations.